Recurrent bilateral frontal lobe lesion with maladaptive schema modes and PTSD symptoms: a case study - Sabir Zaman; Kehkashan Arouj; Shahid Irfan (Journal of the Pakistan Medical Association, 2020)
Abstract The frontal lobe is responsible for high-order functioning, such as memory, attention, decision-making, and personality. Lesions in the frontal lobe may lead to different physical and psychological problems. The current study was conducted to examine the emotional, cognitive, and behavioural states and coping strategies of a patient with recurrent bilateral frontal lobe lesion. It also attempted to determine post-traumatic stress disorder (PTSD) symptoms in a patient. This study described the case of an adult with recurrent bilateral frontal lobe tumour. It covered the clinical presentation, administration of Urdu translation of the Schema Mode Inventory (SMI) and Clinician-Administered PTSD Scale for DSM-5 (CAPS-5), and analysis of the case. The results of the study showed that the recurrent bilateral frontal lobe brain tumour patient engaged in child mode and had a dysfunctional coping style and a maladaptive punitive parent mode. Furthermore, the patient also had moderate PTSD symptoms. Continuous....